Behavior and modeling of double-skin tubular columns filled by ultra-lightweight cement composites (ULCCs). (1st May 2021) - Li, Pengda; Hu, Jingjing; Xing, Feng; Sui, Lili; Zhou, Yingwu; Chen, Cheng
Abstract: Double skin tubular columns (DSTCs) filled by ultra-lightweight cement composites (ULCCs), as primary load-bearing elements, are a practical and reasonable structural asset in lightweight civil infrastructure. This DSTC-ULCC system combines the advantages of three materials, 1) outer fiber-reinforced polymer (FRP) 1–3 ply jackets, 2) filled ULCCs, and 3) inner steel tubes to achieve lightweight, high strength and superior ductility. This article presents an experimental study on the mechanical behavior of DSTCs with FRP and ULCCs under axial compressive loading. The experiment designed a total of 26 DSTCs that were all filled with ULCCs. The key parameters were the number of FRP layers and the inner steel tube properties, (i.e., thickness and diameter of the steel tube). The test results indicate that the properties of the inner steel tube not only influences the effective FRP rupture strain ratio but also the ultimate axial strain of confined ULCCs. This calls attention to the inward buckling behavior for larger void ratios; moreover, thinner steel tubes result in more axial deformation of ULCC-filled DSTCs. In addition, ULCCs showed a much lower elastic modulus compared with normal concrete, which helped cause the change of transition stress of ULCCs in DSTCs, and FRP confinement can effectively increase the elastic length of the stress–strain curves for ULCCs. The experimental results are subsequently compared with predictions from an FRP-confined ULCC model, which led to a new ultimate strain model proposed herein for ULCC-filled DSTCs. The comparison demonstrates that the model can provide reasonably accurate predictions of the stress–strain curves of ULCCs in hollow DSTCs.